The Effect of Positive Management Approach on the Success of Students - Toremen, Fatih; Sanli, Onder (Wydawnictwo Adam Marszalek, 2011)
The purpose of this research was to determine the effects of positive managment approach on the success of students at elementary schools in Malatya central province. We wanted to find out the answers to some questions like: how is positive management understood by administrators of elementary schools, how is this understanding level practised at elementary schools and we also wanted to find out how students and teachers are affected by the management knowledge of school administrators. The sample of the research consists of elementary school teachers who work in different schools of the central province of Malatya. 400 elementary school teachers who work in 30 different schools participated in the research. The schools were chosen according to their success in the school year 2006-2007. 10 most successful elementary schools, 10 medium level successful elementary schools and 10 less successful elementary schools were choosen from among the elementary schools in the central province of Malatya as the the subjects of the research.
Keywords: Optimism; Health; Pessimism